Facial traumas among females through violent and non-violent mechanisms - Costa,Mário César Furtado (2014)
INTRODUCTION: Injuries stemming from facial trauma have both physical and emotional consequences among affected individuals as well as an economic impact on the healthcare system. OBJECTIVE: The aim of this retrospective study was to determine the occurrence of facial trauma among females of different age groups treated at an urgent care ward in the northeast of Brazil in a two-year period. MATERIALS AND METHODS: A cross-sectional study was carried out involving 247 charts. Data on patient age, etiological agent and site of trauma were recorded. RESULTS: Adults accounted for 48.6% of the sample. Falls were the most frequent cause of trauma (38.5%); soft tissue injuries were the most prevalent ones (67.6%); age was significantly associated with the etiology of the injuries; falls were the most common cause among children/adolescents and elderly individuals, and acts of violence were more common among adults. CONCLUSION: Adult females were affected by facial trauma more than the other age groups studied, with a predominance of soft tissue injuries and injuries to the mandible, maxilla, zygomatic arch and nasal bones. Falls were the most prevalent cause of facial trauma and significantly associated with the youngest (children/adolescents) and oldest (elderly individuals) age groups.